Euro Area Policies : 2011 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Member Countries. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
In this study, the risks related to the euro area sovereign debt crisis are analyzed. Methods used to implement the European Financial Stability Facility (EFSF) are overviewed, and the European Stability Mechanism (ESM), the European Systemic Risk Board (ESRB), and the European Supervisory Authority (ESA) are the important framework for financial reforms and macroprudential policies. In this paper, the improvement over the fiscal and structural governance stability and growth pact (SGP) and excessive deficit procedure (SDP) is discussed. Finally, the findings of spillover analysis are outlined.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet